Characterizing damage modes and size effects in high-strength concrete under hydrostatic and triaxial stress states using X-ray microtomography. (13th December 2021) - Williams, Brett; Madra, Anna; Heard, William; Graham, Steven; Grotke, Michael; Hillman, Michael; Nie, Xu
Graphical abstract: Highlights: The deviator stress dictates damage extent more so than hydrostatic pressures. Reduced length-to-diameter ratio affects peak stress and damage propagation. Crack networks become more distributed as confinement pressure increases. End constraint effects are less substantial at high confining pressures (200 MPa). Volumetric strain using a single radial gauge is errant at high axial strains. Abstract: Damage modes are drastically different for concrete under complex stress states. This study investigates damage in high-strength concrete under triaxial loading with confinement pressures up to 200 MPa, while also considering effects from changes in specimen length-to-diameter ratio. Damage was observed and segmented using X-ray microtomography. Hydrostatic pressures up to 200 MPa were fully reversible and caused no detectable damage, thus triaxial deviator stresses dictated damage extent. Brittle failure modes produced shear cracks at angles of 25-30° that became more distributed with increased confinement. Ductile failure modes observed pore collapse with residual strengths being ∼30–50% of pristine strengths.